2001
DOI: 10.4049/jimmunol.166.4.2323
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and CD8+ T Cell Priming for Contact Hypersensitivity Occurs Independently of CD40-CD154 Interactions

Abstract: The primary effector cells of contact hypersensitivity (CHS) responses to dintrofluorobenzene (DNFB) are IFN-γ-producing CD8+ T cells, whereas CD4+ T cells regulate the magnitude and duration of the response. The requirement for CD40-CD154 engagement during CD8+ and CD4+ T cell priming by hapten-presenting Langerhans cells (hpLC) is undefined and was tested in the current study. Similar CHS responses to DNFB were elicited in wild-type and CD154−/− animals. DNFB sensitization of CD154−/− mice primed IFN-γ-produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 49 publications
(57 reference statements)
3
40
0
Order By: Relevance
“…Consistent with previous reports from this laboratory (10,12), the magnitude and duration of CHS responses to DNFB were increased in mice depleted of CD4 ϩ T cells before hapten sensitization compared with responses in mice with the CD4 ϩ T cell compartment intact (Fig. 1A).…”
Section: Increased and Sustained Expansion Of Hapten-primed Cd8 ϩ T Csupporting
confidence: 81%
See 4 more Smart Citations
“…Consistent with previous reports from this laboratory (10,12), the magnitude and duration of CHS responses to DNFB were increased in mice depleted of CD4 ϩ T cells before hapten sensitization compared with responses in mice with the CD4 ϩ T cell compartment intact (Fig. 1A).…”
Section: Increased and Sustained Expansion Of Hapten-primed Cd8 ϩ T Csupporting
confidence: 81%
“…Recent studies from this laboratory indicated that CD4 ϩ T cells negatively influence the stimulatory capacity of LC during priming of hapten-specific CD8 ϩ T cells (12). These results led us to postulate that CD4 ϩ T cells may regulate CHS by restricting the development of effector CD8 ϩ T cells during hapten priming in the skin-draining lymph nodes.…”
mentioning
confidence: 77%
See 3 more Smart Citations